The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1152/japplphysiol.01402.2003
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic evidence of airway opening during recruitment in excised dog lungs

Abstract: The aim of this study was to test the hypothesis that the mechanism of recruitment and the lower knee of the pressure-volume curve in the normal lung are primarily determined by airway reopenings via avalanches rather than simple alveolar recruitments. In isolated dog lung lobes, the pressure-volume loops were measured, and crackle sounds were recorded intrabronchially during both the first inflation from the collapsed state to total lobe capacity and a second inflation without prior degassing. The inflation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
2
16
0
3
Order By: Relevance
“…Measurements of terminal airway resistance (15) and more recent acoustic measurements in collapsed canine lungs during slow-volume recruitment procedures (16) have shown that the recruitment of terminal airspaces are governed by power-law distributions, arising from avalanches associated with threshold phenomena propagating down a branching tree structure. The application of biologically variable respiratory rates and tidal volume have demonstrated superior oxygenation and improved compliance in a porcine oleic acid model of lung injury (14,(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Measurements of terminal airway resistance (15) and more recent acoustic measurements in collapsed canine lungs during slow-volume recruitment procedures (16) have shown that the recruitment of terminal airspaces are governed by power-law distributions, arising from avalanches associated with threshold phenomena propagating down a branching tree structure. The application of biologically variable respiratory rates and tidal volume have demonstrated superior oxygenation and improved compliance in a porcine oleic acid model of lung injury (14,(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…The sudden reopening of closed airways is accompanied by short transient sounds called ''crackles''; these acoustic events can be detected during chest auscultation in a number of lung diseases [24][25][26][27][28][29]. Although crackle sounds have been studied extensively in vitro in collapsed lungs [30][31][32][33], the potential of acoustic measurements for the detection of airway recruitment in vivo has not been exploited. Accordingly, the authors set out to investigate whether the recording of crackles can be used to detect the involvement of airway closure in compromised lung function in vivo.…”
mentioning
confidence: 99%
“…Alterações na composição do surfactante pode diminuir a tensão superficial que, por sua vez, pode levarà formação de pontes líquidas nas vias aéreas respiratórias, dificultando, assim, as trocas gasosas nos sacos alveolares [8,9]. Durante a inspiração, as pontes líquidas que estão bloqueando as vias aéreas, podem se romper devidoàs instabilidades mecânicas [10][11][12] e emitir um ruído discreto denominado de ruído de crepitação [13][14][15], que pode ser facilmente auscultado com um estetoscópio.…”
Section: Agradecimentosunclassified
“…During inspiration, liquid bridges that are closing the airways may pop open due to mechanical instabilities [10,11,12] and emit a discrete sound event called pulmonary crackle, which can easily be heard using a stethoscope. Lung crackle is an important adventitious lung sound for diagnosis of lung diseases [13,14,15,16,17,18] and has been an interesting problem in physics, since they are caused by formation and rapture of capillary liquid bridges [19,20,21,22] which have been studied extensively in other branches of physics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation